Public Perception on Government Spending in Aceh: an Analysis Based on Maqasid Performance Pairwise Matrix (MPPM) - Muhammad Dayyan; Mustafa Omar Mohammed (Share: Jurnal Ekonomi dan Keuangan Islam, 2014)
Governments provide a host of goods and services to their citizens to achieve various socio-economic objectives. Such spending is done through various programs that include social security, education, infrastructure, health and economic. Several conventional approaches for measuring efficiency of government expenditure have been proposed in the literature. Most of these measures are quantitative in nature. For government spending based on Shari’ah oriented public policy (al-Siyasah al-Shar’iyyah), which is value loaded, there is a need for complementary qualitative yardstick to measure whether such spending achieves Maqasid al-Shari’ah. The present study has made use of content analysis to develop a Maqasid Performance Pairwise Matrix (MPPM), as one of the tools of Islamic oriented public policy (al-Siyasah al-Shar’iyyah); to measure the public perception on government expenditure in Aceh in eight areas and the extent to which the expenditure conforms to Maqasid al-Shari’ah. MPPM was used as an instrument to survey 233 respondents in Aceh. The data from the survey were validated analyzed using SPSS version 18.0. The findings from the study are mixed. Government spending in Aceh in Education and health achieved results at the level of Complements (Hajiyat), beyond the basic need (Daruriyat). Whereas in the other six areas, which include economics, public services and housing, government spending is only able to satisfy the basic needs of the Acehnese. The study concludes with recommendations and suggestions for future research. ABSTRAK - Pemerintah menyediakan tempat barang dan jasa untuk warga negara mereka untuk mencapai berbagai tujuan sosial-ekonomi. Seperti pengeluaran, yang dilakukan melalui berbagai program termasuk jaminan sosial, pendidikan infrastruktur, kesehatan dan ekonomi. Beberapa pendekatan konvensional untuk mengukur efisiensi pengeluaran pemerintah telah ada dalam sejumlah literatur. Sebagian besar pendekatan ini bersifat kuantitatif. Untuk belanja pemerintah berdasarkan kebijakan publik yang berorientasi syariah (al-Siyasah al-Shar'iyyah), yang penuh dengan nilai- nilai, ada kebutuhan untuk melengkapi tolok ukur kualitatif untuk mengukur apakah pengeluaran tersebut mencapai Maqasid al-Syari'ah. Penelitian ini menggunakan analisis isi untuk mengembangkan Maqasid Kinerja Berpasangan Matrix (MPPM), sebagai salah satu alat kebijakan publik berorientasi Islami (al-Siyasah al-Shar'iyyah); untuk mengukur persepsi publik atas belanja pemerintah di Aceh pada delapan daerah serta sejauh mana pengeluaran sesuai dengan Maqasid al-Syari'ah. MPPM digunakan sebagai instrumen untuk menyurvei 233 responden di Aceh. Data dari survei ini dianalisis validitasnya dengan menggunakan SPSS versi 18.0. Temuan dari penelitian ini adalah bervariasi. Belanja pemerintah di Aceh dalam bidang pendidikan dan kesehatan mencapai hasil pada tingkat komplemen (Hajiyat), di luar kebutuhan dasar (Daruriyat). Sedangkan di enam daerah lain, yang meliputi ekonomi, pelayanan publik dan perumahan, belanja pemerintah hanya mampu memenuhi kebutuhan dasar masyarakat Aceh. Studi ini memberi kesimpulan dengan rekomendasi dan saran untuk penelitian di masa yang akan datang.